Automatic Signal Indication System through Helmet - Kranthi Madala, Sushma Chowdary Polavarapu , Sri Hari Nallamala, Y. Somesh Teja (International Journal of Advanced Science and Technology, 2020)
In this Day-by-Day increasing population majority of the people will end their lives in road accidents. Generally, many of us forget to turn on the indicating lights while taking a turn (left or right), it may leads to accidents. To overcome this issue this project may find a solution. We will arrange a smart indication signal light module in helmet. Whenever the driver decides to turn a right side he has to move his head to right side once and the module will be connected to bike signal indication system. This will turn on right side signal lights on the bike automatically, similarly left side. The indication will be on condition up to some predefined delay. So we can operate signal lights without any mechanism. Hence this will helps us to reduce those accidents at some extent. It was widely known that Bikes and motorcycles are favoured by younger generations over 4 wheelers. A study uncovers that more than 70 percent of riders are abstaining from wearing helmet for no specific explanation. Moreover speed and alcoholic driving were regular issues. As a result of absence of experience or consideration and traffic rules infringement, serious accidents result. And we make sure, with the aid of technology, that traffic laws are followed, certain issues are avoided and their consequences reduced.